SCREENING OF PRIMARY HYPERPARATHYROIDISM IN PATIENTS WITH UROLITHIASIS - D. S. Rogozin; S. V. Sergiyko; A. A. Rogozina (Вестник хирургии имени И.И. Грекова)
The aim of research was to study the rate of hypercalcemia and primary hyperparathyroidism among patients with urolithiasis. The investigation included 645 patients with urolithiasis. Patients were divided into 2 groups: with normocalcemia and hypercalcemia. The rate of hypercalcemia consisted of 18,9% among patients with urolithiasis. This frequency was 10-20 times higher than in a similar rate of general population. There were no significant differences in age, sex, history of urolithiasis and stone localization between two groups. The data obtained showed an importance of screening of hypercalcemia in patients with urolithiasis regardless the severity of clinical course.